A muscle‐specific MuRF1‐E2 network requires stabilization of MuRF1‐E2 complexes by telethonin, a newly identified substrate. Issue 1 (22nd December 2017) - Polge, Cécile; Cabantous, Stéphanie; Deval, Christiane; Claustre, Agnès; Hauvette, Antoine; Bouchenot, Catherine; Aniort, Julien; Béchet, Daniel; Combaret, Lydie; Attaix, Didier; Taillandier, Daniel
Abstract: Background: Muscle wasting is observed in the course of many diseases and also during physiological conditions (disuse, ageing). Skeletal muscle mass is largely controlled by the ubiquitin‐proteasome system and thus by the ubiquitinating enzymes (E2s and E3s) that target substrates for subsequent degradation. MuRF1 is the only E3 ubiquitin ligase known to target contractile proteins (α‐actin, myosins) during catabolic situations. However, MuRF1 depends on E2 ubiquitin‐conjugating enzymes for ubiquitin chain formation on the substrates. MuRF1‐E2 couples are therefore putative targets for preventing muscle wasting. Methods: We focused on 14 E2 enzymes that are either expressed in skeletal muscle or up‐regulated during atrophying conditions. In this work, we demonstrated that only highly sensitive and complementary interactomic approaches (surface plasmon resonance, yeast three‐hybrid, and split green fluorescent protein) allowed the identification of MuRF1 E2 partners. Results: Five E2 enzymes physically interacted with MuRF1, namely, E2E1, E2G1, E2J1, E2J2, and E2L3. Moreover, we demonstrated that MuRF1‐E2E1 and MuRF1‐E2J1 interactions are facilitated by telethonin, a newly identified MuRF1 substrate. We next showed that the five identified E2s functionally interacted with MuRF1 since, in contrast to the non‐interacting E2D2, their co‐expression in HEK293T cells with MuRF1 led to increased telethonin degradation. Finally, we showed that telethonin governed the affinity between MuRF1 and E2E1 or E2J1. Conclusions: We report here the first MuRF1‐E2s network, which may prove valuable for deciphering the precise mechanisms involved in the atrophying muscle programme and for proposing new therapeutical approaches.